2011
DOI: 10.1038/modpathol.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining patterns of p53 can serve as a surrogate marker for TP53 mutations in ovarian carcinoma: an immunohistochemical and nucleotide sequencing analysis

Abstract: Immunohistochemical staining for p53 is used as a surrogate for mutational analysis in the diagnostic workup of carcinomas of multiple sites including ovarian cancers. Strong and diffuse immunoexpression of p53 is generally interpreted as likely indicating a TP53 gene mutation. The immunoprofile that correlates with wild-type TP53, however, is not as clear. In particular, the significance of completely negative immunostaining is controversial. The aim of this study was to clarify the relationship of the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
414
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(436 citation statements)
references
References 31 publications
17
414
2
3
Order By: Relevance
“…Defining TP53 positivity by an arbitrary cutoff such as 10% makes no sense considering the biological (ie, mutational) correlate for the aberrant or 'all or nothing' staining pattern. 23,26,28 It has been previously shown that diffuse strong TP53 overexpression in at least 50-60% of the tumor Complete absence of staining indicates null mutation, in which a deleterious mutation leads to mRNA, which is degraded by nonsense-mediated decay. 26 Further studies to confirm these associations are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining TP53 positivity by an arbitrary cutoff such as 10% makes no sense considering the biological (ie, mutational) correlate for the aberrant or 'all or nothing' staining pattern. 23,26,28 It has been previously shown that diffuse strong TP53 overexpression in at least 50-60% of the tumor Complete absence of staining indicates null mutation, in which a deleterious mutation leads to mRNA, which is degraded by nonsense-mediated decay. 26 Further studies to confirm these associations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown, the TP53-staining patterns correlate with the mutational status of TP53 ( Figure 1). 23,26 Complete absence of TP53 indicates TP53 null mutation, whereas TP53 overexpression is indicative of TP53 missense mutation, and any staining pattern in between suggests wild-type TP53. The two extreme staining patterns ('all or nothing') are combined as aberrant expression, suggesting any type of TP53 mutation.…”
Section: Tissue Microarray Construction and Immunohistochemistrymentioning
confidence: 99%
“…Absence of p53 nuclear reactivity or nuclear reactivity in ≥ 60% of tumor cells was considered to be an abnormal pattern and suggestive of TP53 mutation. 24 For cases represented by more than one tumor core, absence of p53 nuclear reactivity in all cores or ≥ 60% nuclear reactivity in any core was considered an abnormal pattern.…”
Section: P53 Immunohistochemistrymentioning
confidence: 99%
“…Mota et al (23) investigated the presence of p53 mutations in high-grade serous ovarian carcinomas and reported that the most common p53 mutations were missense mutations; tumors with these mutations had strong and diffuse immunohistochemical p53 positivity. However, the authors defined these tumors as TP53 null cell tumors in the presence of somatic (nonsense, frameshift, and splice junction) p53 mutations, accounting for 30% of all cases, and reported the complete absence of p53 expression by immunohistochemistry in these tumors (23,24); moreover, cases with p53 null mutations had a worse clinical course. In our study, p53 overexpression was found to be statistically significant in the distinction of LMS from benign tumors (p=0.006).…”
Section: Discussionmentioning
confidence: 99%